Somewhere beyond the sea: Human cranial remains from the Lesser Sunda Islands (Alor Island, Indonesia) provide insights on Late Pleistocene peopling of Island Southeast Asia. Issue 134 (September 2019) - Samper Carro, Sofía C.; Gilbert, Felicity; Bulbeck, David; O'Connor, Sue; Louys, Julien; Spooner, Nigel; Questiaux, Danielle; Arnold, Lee; Price, Gilbert J.; Wood, Rachel; Mahirta,
Abstract: The migration of anatomically modern humans (AMH) from Africa to every inhabitable continent included their dispersal through Island Southeast Asia (ISEA) to Australia. Significantly, this involved overwater dispersal through the Lesser Sunda Islands between Sunda (continental Southeast Asia) and Sahul (Australia and New Guinea). However, the timing and direction of this movement is still debated. Here, we report on human skeletal material recovered from excavations at two rockshelters, known locally as Tron Bon Lei, on Alor Island, Indonesia. The remains, dated to the Late Pleistocene, are the first anatomically modern human remains recovered in Wallacea dated to this period and are associated with cultural material demonstrating intentional burial. The human remains from Tron Bon Lei represent a population osteometrically distinct from Late Pleistocene Sunda and Sahul AMH. Instead, morphometrically, they appear more similar to Holocene populations in the Lesser Sundas. Thus, they may represent the remains of a population originally from Sunda whose Lesser Sunda Island descendants survived into the Holocene.